Proceedings of the the 1st International Conference on Computer Science and Engineering Technology Universitas Muria Kudus 2018
DOI: 10.4108/eai.24-10-2018.2280629
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of activated carbon from nyamplung (Calophyllum inophyllum .L) seed shell waste: effect of activation temperature

Abstract: The aims of this research is preparation activated carbon from a waste of seed of nyamplung and to know the surface structure of activated carbon of seed shell and also carbon composition contained in nyamplung seed shell activated carbon. The samples were then sieved with a size of 100 mesh and then carbonated using pyrolysis at 200-400 C for 7 hours, then activated 10 grams using a 30-minute steam pressure with a temperature range from 600 C, 700 C, 800 C and 900 C. The sample was characterized using SEM, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…[5][26] [27] stated that the increase in carbon content in cashew activated carbon is in line with the increase in activation temperature. Furthermore, reinforced by [14] states, with the increase in the activation temperature, the carbon content of the active carbon of nyamplung seeds is high. In this study showed an increase in carbon content before activation and after activation at 700 0 C and 800 0 C.…”
Section: Fig 5 Variation Of the Activation Temperature Of The Carbomentioning
confidence: 99%
See 1 more Smart Citation
“…[5][26] [27] stated that the increase in carbon content in cashew activated carbon is in line with the increase in activation temperature. Furthermore, reinforced by [14] states, with the increase in the activation temperature, the carbon content of the active carbon of nyamplung seeds is high. In this study showed an increase in carbon content before activation and after activation at 700 0 C and 800 0 C.…”
Section: Fig 5 Variation Of the Activation Temperature Of The Carbomentioning
confidence: 99%
“…[13] concluded in temperature activation of coconut shell activated carbon led to an increase in the content of the elements carbon (C), the elements hydrogen (H), oxygen (O), nitrogen (N), and sulfur (S) have decreased with increasing activation temperatures. Likewise, with [14] inactivated carbon nyamplung seed shell. From the explanation that has been described, the researchers are interested in assessing the analysis of the quality of activated carbon from palm bunches using proximate and ultimate characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the effect of activation temperature, which resulted in the evaporation process of volatile matter from the raw material of the activation process [22] [23]. The activation temperature has caused the elemental composition reduced and produces some gas products such as CO, CO2, and hydrogen and methane [24]. For more details on the differences in the pore size of any activation, temperature difference presented in Table 1 and Figure 3.…”
Section: The Effect Of Activation Temperature Variations On Activatedmentioning
confidence: 99%